Sistem Pendukung Keputusan Penentuan Pemberian Pinjaman Dengan Metode Perbandingan Eksponensial (MPE) Pada Koperasi XYZ - Agus Warseno; Yustina Retno Wahyu Utami; Andriani Kusumaningrum (STMIK Sinar Nusantara, 2021)
The XYZ cooperation is a business entity dealing with savings and loans, building rental, convection, rice procurement and shops that are very concerned about the welfare of its members. The appraisal process for loan approval decision in the XYZ cooperative was still lack of assessment. It was based on the value of the members’ report cards which covers collateral, wealth, and behavior so that the funds were not often on the target. Moreover, the cooperative members were often careless in repayment process. The method in this research was Exponential Comparison Method. This method determined the priority order of alternative decisions with criteria. Those criteria in this research were: Report cards, BI Checking, Application Purpose, source of income, monthly income, installment period, completeness of files, guarantees, status, and the amount requested. As a result of applying this system and adding some new criteria, cooperation considers loan approval assessments in determining the eligible members. The results of functional testing by black-box method showed that the system ran as expected and the functions of the application ran properly.